Electrocatalytic Degradation of Rhodamine B on the Sb-Doped SnO2/Ti Electrode in Alkaline Medium - Deng, Dongli; Li, Ying; Wu, Mingzhu; Song, Yang; Huang, Qiongjian; Duan, Yiqin; Chang, Yu; Zhao, Yangyang; He, Chunling (ACS omega, 2023)
To realize efficient electrocatalytic degradation of organic compounds in alkaline wastewater, an Sb-doped SnO2/Ti electrode was fabricated and employed for the removal of Rhodamine B (RhB), and the electrocatalytic oxidation performance of this electrode was assessed in an alkaline medium. In an alkaline solution (pH 11), the complete fading of 50 mg·L–1 RhB could be achieved after 150 min of degradation, the removal efficiency of the chemical oxygen demand reached 56.1% at 300 min, and the degradation process of RhB followed the pseudo-first-order kinetic model very well. Under the attack of hydroxyl radicals, partial RhB was degraded to low-molecular-weight organic acids through N-demethylation and the destruction of the conjugated chromophore. Various techniques including scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and cycle voltammetry were used to examine the changes in the morphology and structure, as well as the activity of the Sb-doped SnO2/Ti electrode before and after use. The Sb-doped SnO2/Ti electrode could be reproduced in batches, and each electrode was reused up to eight times without a significant decrease in degradation ability; the leaching amount of antimony was significantly lower than the national emission standard. The electrocatalytic oxidation of the dye wastewater sample was also performed with the desired results, indicating that electrochemical oxidation is a very promising technology for the treatment of alkaline dye wastewater using a Sb-doped SnO2/Ti electrode.